PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUDIO-VISUAL BERBASIS ANIMASI TEHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SMA NEGERI 14 MEDAN T.A. 2022/2023 - Novrina Chanrutsi; Nurjannah (Melati Institute, 2023)
This study aims to determine the Effect Of Using Animation-Based Audio-Visual Learning Media on Economic Learning Outcomes of class X Students of SMA Negeri 14 Medan T.A 2022/2023. This study used a population of 102 students in class X IPS at SMA Negeri 14 Medan and the sampling technique was by determining the sample so that only one class used as the sample, namely class X IPS-2, which consisted of 35 students from SMA Negeri 14 Medan. The collection technique in this study used tests given to students. The results of the research are in accordance with the hypothesis formulated in this study, the truth can be accepted, because tcount ? ttable or 3,17 ? 1.676. it can be interprented that thee is a positive and significant influence between students understanding of using audio-visual animation media on student learning outcomes in learning management in class X SMA Negeri 14 Medan.